Energy efficient clustering strategies for wireless sensor network - Hew, Chong Lip. (2013)
The project is about the investigation and simulation for some of the routing protocols used in Wireless Sensor Network (WSNs). Frequently wireless sensors are deployed in the real world to monitor and regulate the environment situation. To transmit the data obtained from the wireless sensors, electrical power are essential for their operations as well as to process the sensed information to communicate with other sensor nodes and base station. As a result, lifetime of the network is only as long as the lifetime of the sensors. Consumption of battery power is highly dependent on the performance of the network routing protocols. One of the fundamental factors for a high lasting lifetime of the network lies in the efficiency of routing protocol of the WSN. One way to improve the lifetime of the network is by using hierarchical routing protocol that groups sensors in the network into clusters. By using hierarchical routing, the maximum hop count from the lowest level sensors to the highest level sink is limited to only 2. Hierarchical routing protocol increases routing efficiency of WSN as it has few routing advertisement and at the same time simplify the complexity on the topology of the network. A hierarchical routing protocol; Low Energy Adaptive Clustering Hierarchy (LEACH) will be explored and implemented to examined and evaluate the performance of the network. LEACH group sensors into cluster, each with a CH having the role of transmitting aggregated data to the sink (base station). LEACH uses Carrier Sense Multiple Access (CSMA) to form cluster, and uses Time Division Multiple Access (TDMA) to communicate between CM and CH. In this project, Omnet++ is used to simulated an environment deploy with 100 wireless sensors. The characteristic and advantages of LEACH are also discussed in the paper. The setup is then integrated with energy harvesting capabilities to determine the performance of LEACH-EH as well as the implications of this newly proposed sensor network.